Peran the International Committee of the Red Cross (ICRC) pada Perlindungan Jurnalis Korban Perang Menurut Hukum Humaniter International - Ihsan, Rama Fatihul (UM Purwokerto Press, 2024)
This article examines the role of the International Committee of the Red Cross (ICRC) in protecting journalists who are victims of war under international humanitarian law. The protection of journalists in armed conflict is an important issue given their role in conveying information to the public. International humanitarian law, through various instruments such as the Geneva Conventions and their Additional Protocols, emphasizes the need for special protection for journalists who are not involved in combat. The ICRC, as an independent humanitarian organization, plays a role in ensuring the application of and respect for these legal provisions. This article explores the steps taken by the ICRC, and highlights the challenges and opportunities in improving protection for journalists. The analysis also demonstrates the importance of international cooperation in strengthening compliance with international humanitarian law.